Water Law in Pará State, Brazil: advances, barriers and reflections - Silva, Davi Farias da; Silva, Jaqueline Maria Soares da; Salim, Camila de Mesquita; Sodré, Silvana do Socorro Veloso; Beltrão, Norma Ely Santos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
In Brazil, Law No. 9,433/2007 was responsible for establishing the National Water Resources Policy and the National Water Resources Management System, with the aim of maintaining the quality and quantity of water resources, reducing conflicts due to multiple water uses and increasing the participation of civil society in decision-making on issues related to this resource. In 2001, it was the turn of Pará State to institute its own water resources legislation through State Law No. 6,381/2001, in consonance with federal legislation. The main purpose of this study was to analyze the institution of the Water Law in the State of Pará and to investigate how far the State has managed to implement the entities that make up its State Water Resources Management System and its management instruments. For this reason, a documental research was carried out in the record and resolutions of the State Council of Water Resources of Pará, a advisory, normative and deliberative body and occupant of the highest position within the state system, on the SEMAS website that contains in the Management Body of the state’s water resources policy and in academic papers related to this subject. The results reveal that, even after almost two decades of this legislation, not all entities in the system are instituted, as well as some management instruments were not elaborated, particularly the State Water Resources Plan given its degree of importance.